2015
DOI: 10.1097/ypg.0000000000000078
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the associations between the SLC6A4 promoter polymorphism (5HTTLPR) and the risk for alcohol dependence

Abstract: Serotonin reuptake variation is linked to a functional polymorphism in the promoter region of the SLC6A4 gene on chromosome 17. It is plausible that variations in genetically determined SLC6A4 activity may modify the risk of alcohol dependence. To determine whether this allele is associated with alcohol dependence, the authors conducted a systematic review and a metaanalysis. Twenty five studies with 8,885 participants were included. The meta-analysis was conducted using a random-effects model. Overall, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
(6 reference statements)
0
12
0
1
Order By: Relevance
“…The third showed a significant association of SUDs (including alcohol, heroin and cocaine dependence) with the polymorphism 11. Finally, the most recent meta-analysis did not find an overall association with alcohol dependence, but highlighted several methodological limitations in published studies19 including: inconsistencies in the screening of highly comorbid psychiatric disorders, lack of an adequate control group as many of the studies relied on convenience samples rather than population-based controls, insufficient description of genotyping methods and heterogeneity in case definition.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The third showed a significant association of SUDs (including alcohol, heroin and cocaine dependence) with the polymorphism 11. Finally, the most recent meta-analysis did not find an overall association with alcohol dependence, but highlighted several methodological limitations in published studies19 including: inconsistencies in the screening of highly comorbid psychiatric disorders, lack of an adequate control group as many of the studies relied on convenience samples rather than population-based controls, insufficient description of genotyping methods and heterogeneity in case definition.…”
Section: Introductionmentioning
confidence: 90%
“…An a priori decision was made not to correct for multiple testing as conditions in which a correction for multiple testing is necessary are still a matter of controversy. It has been suggested that in exploratory analyses of a genetically complex trait in which the relationship between genotype and phenotype has not yet been established,11 17–19 44 multiple test adjustments are not strictly required45 since they may increase the likelihood that actual effects would be missed (type II error rates) 46…”
Section: Methodsmentioning
confidence: 99%
“…A limitation of this study is that the groups were not appropriately matched according to age and years of education, which could have had an impact on the study results. We compensated for potential gender differences in drinking behavior [70,71] by including only male subjects, thus further increasing the strength of our study, although a recently published meta-analysis found no influence of sex and SLC6A4 5-HTTLPR on alcohol dependence [72]. Our study was also not biased by genetic heterogeneity, since we included only Slovenian subjects recruited in a geographic area with an ethnically homogeneous Caucasian population [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a meta-analysis of 25 case control studies (n=8885) found no link between 5-HTTLPR polymorphism and alcoholism (Villalba et al 2015). In a German study conducted among 250 institutionalized alcoholics and 94 healthy controls, no significant differences were observed with respect to S and L allele genotypes between the two groups (Kohnke et al 2006).…”
Section: -Httlpr Polymorphism and Alcohol Use Problemsmentioning
confidence: 99%